SISTEM PEWARISAN KESENIAN TALEMPONG PACIK DALAM MASYARAKAT NAGARI PAUH KAMANG MUDIAK, KABUPATEN AGAM - Prayudha, Angga; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
ABSTRACT The purpose of this study is to reveal the traditional musical inheritance system of talempong pacik by traditional artists from the village Pauh Kamang Mudiak. The type of research was qualitative research. The main instrument in the study was the researcher and it was assisted by supporting instruments such as stationery, photo and video camera. Techniques of data collection were carried out by doing observation, interview and literature study. The type of data were primary and secondary data. Techniques of analysis data were done by collecting, classifying and making data conclusions. The result shows that inheritance system of talempong pacik arts through training in one of the studios in the Pauh Kamang Mudiak village, where the inheritance of talempong pacikcould  can be learned by all the community of  Pauh Kamang Mudiak village. The inheritance process can also be carried out in a community and family environment where parents provide a direct introduction to their children toward talempong pacik arts which is held in the community environment through traditional arts performance events. In order that the inheritance process to run effectively, artists and teenagers arrange a good schedule for the training process so that the talempong pacik arts can develop and its preservation is maintained until the next generation. Keywords: system, inheritance, Talempong Pacik